Pondok Pesantren Anak Jalanan At-Tamur Cibiru Hilir Bandung - Jatmika Aji Santika; Fajriudin Fajriudin; Dina Marliana (UIN Sunan Gunung Djati Bandung, 2022)
Pondok Pesantren is the oldest educational institution in Indonesia, along with the development of the Islamic boarding school era, it has also undergone changes adapted to the development and needs of the times without eliminating the traditions and traditional values in the Islamic boarding school. Today's Islamic boarding schools also adopt a modern education system and incorporate scientific methods into it, besides that, if in the past the pesantren was intended for students who were entrusted by their parents, now there is a boarding school that not only accommodates students who are entrusted to it, but the pesantren also accommodates children. -Street children who do not have parents and want to study, then want to know about religious knowledge and practice it.